Technical aspects of distal pancreatectomy with splenic preservation - Rocha, Artur Jorge de Barros (2017)
Due to increased experience in laparoscopic surgery and the availability of new technological devices, Laparoscopic distal pancreatectomy (LDP) has gained worldwide acceptance, and is currently accepted as an alternative to the open thecnique in the treatment of distal pancreatic tumors. In patients with benign or low grade malignancies, LDP is described as a feasible and safe procedure. Decreased blood loss and morbidity, early recovery and shorter hospital stay are some of the main advantages of this approach. However, there is no standardized thecnique for this procedure. The authors present the thecnical aspects of LDP with spleen and splenic vessels preservation, highlighting some important aspects of this approach, in order to potencially optimize its results.